The Effect of Nanocurcumin Size Inhibitory Effect on Klebsiella pneumoniae and Staphylococcus aureus Bacteria - Suak, Raffael Griffin Frarie; Ricky, Donn Richard; Tobing, Joshua Hamonangan Lumban (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Bacterial infections such by Staphylococcus aureus and Klebsiella pneumoniae remain a major health challenge due to the increasing problem of antibiotic resistance. Curcumin has shown antibacterial potential; however, its poor solubility and low bioavailability limit its effectiveness. This study aimed to analyze the effect of varying PVP K30 concentrations on the particle size of nanocurcumin and its inhibitory activity against both bacteria. A true experimental design with a posttest-only control group was employed using three concentrations of PVP K30: 1.5 g/mL, 3.0 g/mL, and 4.5 g/mL. Particle size was measured using a Particle Size Analyzer (PSA), while antibacterial activity was evaluated through the disk diffusion method on Mueller-Hinton Agar (MHA). The results showed that increasing PVP K30 concentration reduced particle size, with mean diameters of 132.2 nm, 295.2 nm, and 20.6 nm, respectively. The inhibition zones by S. aureus ranged from 1.82–3.6 mm (weak), while those by K. pneumoniae ranged from 1,08–8,98 mm (weak to moderate). ANOVA analysis indicated no significant effect on S. aureus (p= 0.099 > α= 0.05), but a significant effect on K. pneumoniae (p= 0.000 < α= 0.05). These findings suggest that nanoparticle size plays an essential role in enhancing the antibacterial activity of nanocurcumin, particularly against Gram-negative bacteria.